Ashanti Proverbs (The Primitive Ethics of A Savage People) Tr. From The Original With Grammatical and Anthropological Notes - R. S. (Robert Sutherland). ed. and tr Rattray (Oxford, The Clarendon press, 1916)
This book, Ashanti proverbs (the primitive ethics of a savage people) tr. from the original with grammatical and anthropological notes, by Rattray, R. S. (Robert Sutherland), 1881-1938. ed. and tr,Christaller, Johann Gottlieb, 1827-1895, is a replication of a book originally published before 1916. It has been restored by human beings, page by page, so that you may enjoy it in a form as close to the original as possible. This book was created using print-on-demand technology. Thank you for supporting classic literature.